Análise da aplicação das diretrizes públicas de educação ambiental em área de mananciais: estudo de caso do município de Piraquara/PR - Rodrigues, Ana Paula da Silva (2018)
Environmental Education gains momentum around the 1970's upon the realisation of international conferences focused on fighting the environmental crisis evidenced worldwide. By the end of the 20th century and the beginning of the 21st, teaching it became compulsory in Brazil, with the establishment of national public educational guidelines on Environmental Education, with directives towards its introduction in the formal arena. Today's socialenvironmental scenario affirms a model, which has become unsustainable through the times given the intensive exploration and degradation of natural resources that made possible the existence, with quality, of the most varied forms of life in our planet. On this train of thought, this dissertation is justified by the relevance shown by the EE towards the educational context and the gaining of new knowledge, values, wisdom and environmentally appropriate practices, looking to promote an ecologically balanced environment to the present and future generations, as recommended by our Federal Constitution. This research is characterised by a case study around the public EE directive in the Brazilian city of Piraquara, in the State of Paraná, one of Curitiba's (the State's capital city) satelite towns, modelled as an applied research of a qualitative, explanatory and field nature. Its main objective is to analyse the application of these directives and how they are articulated within the schools that are part of the Public Municipal Education Network. The methodology applied uses both comparative and content documental analysis, with data collection through institutional documents, questionnaires and interviews. From the perspective of user support, the national educational and EE directives, as well as the environmental protection in the area, are proven fragile within the public schools in this region. As such, we conclude that the EE focused towards school environments have not been satisfactory in forming the critical awareness within the students desired in order to promote the environmental protection in the municipal territory, especially in its springs area, and the environment as a whole as a last resort.